Konflik Sosial Kegamaan di Pati: dari Motif Teogenetis ke Sosiogenetis atas al Quran dan Hadis - Mukhamad Agus Zuhurul Fuqohak, Mukhamad Agus Zuhurul Fuqohak Zuhurul (FIKRAH, 2021)
This article aims reveal the conflicting motives for understanding the coran and Hadith in Sundoluhur Pati Village, Indonesia. This article uses a phenomenological approach for looking through interviews with five charismatic peoples. This paper uses theory of motives and Bourdieu's theory of habitus, capital and arena. Motive theory is used to reveal the nature and characteristics of the problems, and Bouerdie's theory analyzes the developing problems in order to detect the modals used in arguing. The finding of the article is that the conflict began when the study of the Coran and Hadith with the books of al-Muwafaqat and al-I'tisham by Imam as-Syâthibi could be categorized as a theogenetic motif. The power desired by some figures and the community is a sociogenetic motive because of the community's push for religious leaders to return to old traditions.